Preservation of capsular transparency and geometrical consistency in cataract surgery using a novel intracapsular ring - Ahmed Elmassry; Onurcan Sahin; Loukia Leonidou; Dimitris Liakopoullos; Harilaos Ginis; Aristophanis Pallikaris; Ioannis Pallikaris (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
We report a case of a patient that was implanted with an intracapsular ring during phacoemulsification cataract surgery. Namely, we report on refraction, posterior capsule transparency and IOL ACD and document photographically the appearance of the posterior capsule. It is suggested that the presence of the intracapsular ring has inhibited epithelial cell migration and prevented the formation of posterior capsule opacification (PCO) in the postoperative interval of 7 months. A comparison with the fellow eye of the same patient is made.